Prilaku Pendanaan dan Resiko Kebijakan pada Perusahaan Kelautan di Bursa Efek Indonesia - Asmaul Husna; Myrna Sofia (Jurnal Kajian Akuntansi dan Auditing, 2020)
This study aims to determine the risk of policies, company-specific characteristics that have an impact on the behavior of marine company financing in Indonesia. Samples were obtained using purposive sampling and obtained 16 samples of Marine companies that were Listed on the Indonesia Stock Exchange in the 2015-2018 Period. The data in this study were processed using the Stata 14.0 application. And the estimation method in this research is to use the random effect method. The results of this study for the independent variable risk policy consisting of EPU (economic policy uncertainty) and GPR (political risk) do not affect all types of funding, both debt, capital and actual financing. While the independent variable IOS has no significant effect on the three types of financing used, and cash flow variable has a significant effect on debt financing and actual financing while capital financing does not. Sales growth has a significant effect on the type of debt financing at alpha 5%, while actual financing has a significant effect on alpha 10% and has no effect on capital financing.